Ethics in international health research: a perspective from the developing world - Bhutta Zulfiqar Ahmed (The World Health Organization, 2002)
Health research plays a pivotal role in addressing inequities in health and human development, but to achieve these objectives the research must be based on sound scientific and ethical principles. Although it is accepted that ethics play a central role in health research in developing countries, much of the recent debate has focused on controversies surrounding internationally sponsored research and has taken place largely without adequate participation of the developing countries. The relationship between ethical guidelines and regulations, and indigenously sponsored and public health research has not been adequately explored. For example, while the fundamental principles of ethical health research, such as community participation, informed consent, and shared benefits and burdens, remain sacrosanct other issues, such as standards of care and prior agreements, merit greater public debate within developing countries. In particular, the relationship of existing ethical guidelines to epidemiological and public health research merits further exploration. In order to support health research in developing countries that is both relevant and meaningful, the focus must be on developing health research that promotes equity and on developing local capacity in bioethics. Only through such proactive measures can we address the emerging ethical dilemmas and challenges that globalization and the genomics revolution will bring in their wake.